Pengaruh Model Pembelajaran Jigsaw Terhadap Keaktifan Belajar Pendidikan Agama Kristen Siswa Kelas XI SMA Swasta HKBP 2 Tarutung Tahun Pembelajaran 2023/2024 - Jeremia J. Hutajulu; Dorlan Naibaho; Frainskoy Rio Naibaho; Tiurma Barasa; Sabar Rudi Sitompul (Jurnal Pendidikan Agama dan Teologi, 2024)
The aim of this research is to determine the positive and significant influence of the Jigsaw learning model on the active learning of Christian Religious Education of class XI students at HKBP 2 Tarutung Private High School for the 2023/2024 academic year. The research method used is a quantitative method with inferential statistics. The population is all class Data was collected using a positive closed questionnaire with 42 items, namely 22 items for variable 2023/2024 learning, proven through the following data analysis: 1) Test the analysis requirements: a) positive relationship test obtained by the value rxy = 0.586 > rtable (=0.05,n=42) = 0.304. b) Testing a significant relationship obtained tcount= 4.572 > ttable(=0.05, dk=n-2=40)= 2.021. 2) Influence test: a) Regression equation test, obtained the regression equation =24,76+0,57X . b) Regression coefficient of determination test (r2) = 34.3%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(=0.05, dk numerator k=22, dk denominator=n-2=42-2=40) namely 20.90 > 1.51. Thus Ha is accepted and H0 is rejected